Perceptions of Intermediate-Level Public School Teachers in Implementing the Catch–Up Friday Program - Jaris May Ganohay; April May Gargar; Georgina Cortes; Welma Balang; Francis May Valmorida; Alfer Jann D. Tantog (Research Synergy Foundation, 2025)
This study explored intermediate-level public school teachers’ perceptions of the implementation of the Catch-Up Day program, a remedial initiative designed to support struggling learners by providing additional instructional time. The program bridges learning gaps and enhances students’ reading and comprehension skills. Specifically, the study aimed to (1) examine teachers’ perceptions of the program, (2) explore its implementation in public schools, (3) identify challenges faced, (4) determine coping strategies, (5) examine the program’s impact on teachers' experiences (6) assess its effectiveness, (7) gather recommendations for improvement. A single case study method was used, involving six (6) intermediate-level teachers from Grades 4 to 6 from a public school in Pagadian City, Zamboanga, Del Sur. Data were collected through interviews guided by an Interview Guide, conducted in a quiet school office after class hours to minimize disruptions, and analyzed using categorical aggregation, clustering data into categories to identify patterns. Findings revealed that teachers viewed the program positively and recognized its benefits despite the additional workload. Key strategies included sharing lesson plans, interactive activities, reinforcing basic reading skills, implementing peer tutoring, and incorporating enhancement activities. Challenges such as increased workload, poor reading comprehension, lack of parental support, and low student interest were managed through supplementary materials, take-home activities, parental communication, and interactive reading sessions. Teachers affirmed the program’s effectiveness in improving reading skills and emphasized the need for adequate resources and support. This study’s findings provide insights for educators, administrators, and policymakers to enhance programs and address the needs of both teachers and students.